Nematodes and Microorganisms Interactively Stimulate Soil Organic Carbon Turnover in the Macroaggregates - Jiang, Yuji; Zhou, Hu; Chen, Lijun; Yuan, Ye; Fang, Huan; Luan, Lu; Chen, Yan; Wang, Xiaoyue; Liu, Manqiang; Li, Huixin; Peng, Xinhua; Sun, Bo (Frontiers in Microbiology, 2018)
The intra-aggregate architecture of soil macroaggregates provides suitable microhabitats for nematodes to graze on microorganisms. However, it is not fully clear how nematodes and microbial communities interactively mediate soil organic carbon (SOC) turnover. Here, we aimed to illustrate the relationships between nematodes, microbial community, and SOC turnover in the macroaggregates of a red soil receiving long-term manure application. Soil macroaggregates (>2 mm) were sampled from an 11-year field experiment including four manure treatments: no manure (M0), low manure rate (M1), high manure rate (M2), and high manure rate with lime (M3). The abundances of nematodes and microbial communities were substantially increased under manure treatments. Bacterivores dominated under the M2 and M3 treatments, while plant parasites were enriched under the M1 treatment. Phospholipid fatty acid analysis indicated that the ratio of bacteria to fungi significantly increased, but the ratio of Gram-positive bacteria to Gram-negative bacteria declined with the increasing manure addition. Random forest modeling showed that soil porosity had a primary effect on nematode assemblages, while pH and SOC contributed profoundly to the structure of the microbial community and carbon metabolic capacity. Structural equation modeling suggested that nematode grazing promoted carbon metabolic activities predominantly due to increased microbial biomass. Taken together, the mechanistic understanding of nematode-microorganism interactions may have important implications for improving soil fertility by nematode-mediated microbial processes.